Developing a guideline for measuring workplace non-Gaussian noise exposure based on kurtosis adjustment of noise level in China - Zhang, Meibian; Hu, Yong; Qiu, Wei; Gao, Xiangjing; Zeng, Anke; Shi, Zhihao; Xin, Jiarui; Bai, Shixing; Sun, Xin (Frontiers in Public Health, 2022)
Objective There is no unified standard for measuring workplace non-Gaussian noise (known as complex noise) exposure. This study aimed to develop a draft guideline for measuring workplace non-Gaussian complex noise exposure based on noise temporal structure adjustment. Methods Noise exposure level, e.g. the A-weighted sound pressure level normalized to a nominal 8-hour working day (LEX,8h), was adjusted using the temporal structure (expressed by kurtosis) of noise. Noise waveform analysis or the instrument’s direct reading was used. Results The framework of the draft guideline included measurement metrics, the protocol using kurtosis to adjust LEX,8h, technical requirements for measuring instruments, measurement steps, data analysis, and measurement recording. Conclusion The draft guideline could provide a basis for accurately measuring workers’ exposure to non-Gaussian noise and assessing the occupational hearing loss associated with non-Gaussian noise.